2016
DOI: 10.13004/kjnt.2016.12.2.72
|View full text |Cite
|
Sign up to set email alerts
|

A Faster and Wider Skin Incision Technique for Decompressive Craniectomy: n-Shaped Incision for Decompressive Craniectomy

Abstract: ObjectiveDecompressive craniectomy (DC) is a useful surgical method to achieve adequate decompression in hypertensive intracranial patients. This study suggested a new skin incision for DC, and analyzed its efficacy and safety.MethodsIn the retrograde reviews, 15 patients underwent a newly suggested surgical approach using n-shape skin incision technique (Group A) and 23 patients were treated with conventional question mark skin incision technique (Group B). Two groups were compared in the terms of the decompr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 20 publications
(8 citation statements)
references
References 10 publications
0
6
0
2
Order By: Relevance
“…This "n-type" incision is mostly used in patients with SAH previously treated by operative clipping. 28 The incision starts perpendicular to and at the middle of the previous frontotemporal incision and runs posteriorly to reach the inion, after which it curves laterally in the direction of the mastoid base. The "T-type" or "Kempe" incision was abandoned before 2010 due to frequent wound healing problems at the intersection of both linear incisions.…”
Section: Incision Typesmentioning
confidence: 99%
“…This "n-type" incision is mostly used in patients with SAH previously treated by operative clipping. 28 The incision starts perpendicular to and at the middle of the previous frontotemporal incision and runs posteriorly to reach the inion, after which it curves laterally in the direction of the mastoid base. The "T-type" or "Kempe" incision was abandoned before 2010 due to frequent wound healing problems at the intersection of both linear incisions.…”
Section: Incision Typesmentioning
confidence: 99%
“…Meticulously preserving the superficial temporal artery and limiting the posterior extent of the flap to no more than 5 cm behind the ear could reduce chance of ischemic flap breakdown. A retrospective comparison of patients operated using an n-shaped incision with those who were operated using the conventional question mark flap showed that the former technique could accomplish greater bony decompression, allows more brain protrusion and is faster to perform ( 28 ). We have noticed that making a retroauricular incision could also reduce flap necrosis.…”
Section: Early Complicationsmentioning
confidence: 99%
“…However, combined orbital and temporal fractures in the setting of multiple ICH called for a large, single question-mark style incision to expose the extent of both fractures and permit exposure and evacuation of ICH. Yang et al recently discussed how a smaller, "n-shape" incision may permit at least equal utility for decompressive craniectomy [14]. Potential benefits of novel approaches for reconstructive craniotomy of the temporal-orbital area, especially in the setting of complex fractures, require future investigation.…”
Section: Discussionmentioning
confidence: 99%